Ontogenetic variations of the head of Aptenodytes forsteri (Aves, Sphenisciformes): muscular and skull morphology - Sosa, María Alejandra; Acosta Hospitaleche, Carolina Ileana Alicia (Polar Biology)
The emperor penguin (Aptenodytes forsteri) is the largest extant penguin among living species breeding in winter, at Antarctic high latitudes. Despite several studies made on this species, musculature and skeletal anatomy are barely known, especially in non-adult specimens. To address this shortfall, dissections and comparative descriptions were made on crania and mandibles of individuals of different ontogenetic stages: chicks, juveniles, and adults. The results presented here show significant differences in musculature between the age groups, and the proportions between bill and cranium also change along postnatal ontogeny. Fil: Sosa, María Alejandra. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Acosta Hospitaleche, Carolina Ileana Alicia. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina